Mental health experiences of HIV/TB healthcare workers during the COVID-19 pandemic - lessons for provider well-being and support from a qualitative study in seven South African provinces - Blia Yang; Rafaela Egg; Heena Brahmbhatt; Mahlodi Matjeng; Thanduxolo Doro; Zandile Mthembu; Batanayi Muzah; Brendon Foster; Johanna Theunissen; Ashley Frost; April Peetz; Katie Reichert; et al. (BMC, 2023)
Abstract Background COVID-19 has substantially reshaped health service delivery. Healthcare workers have had to serve more clients, work longer shifts, and operate in conditions of uncertainty. They have experienced multiple stressors related to the additional 'labour of care', including managing the frustration of inadequate therapeutic or symptom relief options, witnessing clients dying, and having to give this news to clients' family members. Ongoing psychological distress among healthcare workers can severely undermine performance, decision-making and well-being. We sought to understand the impact of the COVID-19 pandemic on the mental health experiences of healthcare workers delivering HIV and TB services in South Africa. Methods We used a pragmatic and exploratory design to understand HCWs' mental health experiences with in-depth qualitative data. We implemented the study in ten high HIV/TB burden districts across seven of South Africa's nine provinces among healthcare workers employed by USAID-funded implementing partners. We conducted in-depth interviews (virtual) with 92 healthcare workers across 10 cadres. Results Healthcare workers reported experiencing a range of extreme and rapidly fluctuating emotions because of COVID-19 that negatively impacted on their well-being. Among these, many healthcare workers report experienced a great deal of guilt at their inability to continue to provide quality care to their clients. In addition, a constant and pervasive fear of contracting COVID-19. Healthcare workers' stress coping mechanisms were limited to begin with, and often further interrupted by COVID-19 and non-pharmaceutical response measures e.g., 'lockdowns'. Healthcare workers reported a need for greater support for managing the everyday burden of work - not only when experiencing a mental well-being 'episode'. Further, that whenever they were exposed to stressor events, e.g., supporting a child living with HIV who reports sexual abuse to the healthcare worker, that this this would trigger additional support interventions and not rely on the healthcare worker seeking this out. Further, that supervisors spend more effort demonstrating appreciation toward staff. Conclusions The COVID-19 epidemic has added significant mental health burden for healthcare workers in South Africa. Addressing this requires broad and cross-cutting strengthening of everyday support for healthcare workers and centring staff's mental well-being as core to delivering quality health services.